Evaluation of a carbon paste electrode modified with organofunctionalised SBA-15 silica in the determination of copper - Cesarino, Ivana; Marino, Glimaldo; Matos, Jivaldo do Rosário; Cavalheiro, Éder Tadeu Gomes (Eclética Química, 2007)
The performance of a carbon paste electrode (CPE) modified with SBA-15 nanostructured silica organofunctionalised with 2-benzothiazolethiol for determination of Cu(II) ions in sugar cane spirit (cachaça) is described, based on differential pulse anodic stripping voltammetry (DPASV) procedure. The Cu(II) oxidation peak was observed at – 0.03 V (vs. SCE) in phosphate solution (pH 3.0). The results were obtained using optimised conditions such as 100 mV pulse amplitude, 3 min accumulation time, 25 mV s -1 scan rate in phosphate solution pH 3.0, resulting in a linear dynamic range from 8.0 x 10 -7 to 1.0 x 10 -5 mol L -1 Cu(II) and a limit of detection 2.0 x10 -7 mol L -1 . Cu(II) spiked in a cachaça sample was determined with 102.5 % mean recovery at mmol L -1 level. Interference from other metallic cations present in the sample was avoided by the standard addition procedure.